2007
DOI: 10.1021/jf062680g
|View full text |Cite
|
Sign up to set email alerts
|

Food-Grade Mulberry Powder Enriched with 1-Deoxynojirimycin Suppresses the Elevation of Postprandial Blood Glucose in Humans

Abstract: Mulberry 1-deoxynojirimycin (DNJ), a potent glucosidase inhibitor, has been hypothesized to be beneficial for the suppression of abnormally high blood glucose levels and thereby prevention of diabetes mellitus. However, DNJ contents in commercial mulberry products were as low as about 0.1% (100 mg/100 g of dry product), implying that the bioavailability of DNJ might not be expected. We carried out studies in two directions: (1) production of food-grade mulberry powder containing a maximally high DNJ content; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
256
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(267 citation statements)
references
References 20 publications
9
256
0
2
Order By: Relevance
“…[8][9][10][11] Yatsunami et al have reported the relationship between the -glucosidase inhibitory activity and 1-DNJ concentration from a group of species, 10) but not enough is known about -glucosidase inhibitors other than 1-DNJ from each cultivar. Since the -glucosidase inhibitory activity was not consistent with the 1-DNJ concentration in several cultivars, it is thought that -glucosidase inhibitors besides 1-DNJ were involved in the effective defense by mulberry plants against insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Yatsunami et al have reported the relationship between the -glucosidase inhibitory activity and 1-DNJ concentration from a group of species, 10) but not enough is known about -glucosidase inhibitors other than 1-DNJ from each cultivar. Since the -glucosidase inhibitory activity was not consistent with the 1-DNJ concentration in several cultivars, it is thought that -glucosidase inhibitors besides 1-DNJ were involved in the effective defense by mulberry plants against insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…The typical cultivars of mulberry plants are maintained and administered in Japan at the National Institute of Agrobiological Sciences (Tsukuba, Ibaraki, Japan) and the Experimental Farm of Textile Science and Technology of Shinshu University (Ueda, Nagano, Japan). It has been reported that the -glucosidase inhibitory activity and 1-DNJ concentration of mulberry leaves differ among various cultivars and seasons, [8][9][10][11] but it is unknown which environmental conditions influence the -glucosidase inhibitory activity. We therefore investigated in this study the relationship between the environmental conditions and -glucosidase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…From the results obtained, all formulations had a swelling time of <1 minute. This result could be explained by the fact that the cross-linking time was not long (15 minutes), so it caused the beads to swell quickly [5,6]. Furthermore, pectin was used as the polymer, and it is a hydrophilic polymer, so it can absorb water.…”
Section: Swelling Timementioning
confidence: 99%
“…A previous study showed that mulberry leaf extract had an anti-diabetic effect in diabetes-induced Wistar rats [4,5]. Mulberry leaves (Morus alba L.) contain 1-deoxynojirimycin and its derivatives, an intestinal glucosidase inhibitor that prevents the hydrolysis of carbohydrates to monosaccharide, and therefore, suppresses the blood glucose level [6]. Mulberry leaf extract has been formulated as an effervescent tablet, whitening cream, and capsule.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of mulberry, as a folk medicine, has been traditionally used in Asian countries for purposes to treat fever, protect the liver, improve eyesight, strengthen joints, facilitate the discharge of urine, reduce blood glucose and lower blood pressure [1]. Mulberry leaves extracts have shown multi-direction biological activities, such as the antioxidant, antimicrobial, anti-inflammatory, anti-allergic, anti-atherosclerotic, and significant hypoglycemic effect [2][3][4][5][6][7]. A large amount of polysaccharides was contained in mulberry leaves, and their useful pharmacological effects, such as hypoglycemic and lipid-lowering activities, have been verified [8].…”
Section: Introductionmentioning
confidence: 99%